2022
DOI: 10.3390/cells11152446
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Fatty Acid Profiles of New Pinnularia (Bacillariophyta) Species from Soils of Vietnam

Abstract: We studied the morphology, ultrastructure, and phylogeny of eight soil diatom strains assigned to the Pinnularia genus. Six of these strains, identified by us as new species, are described for the first time. We provide a comprehensive comparison with related species and include ecological data. Molecular phylogeny reconstruction using 18S rDNA and rbcL affiliates the new strains with different subclades within Pinnularia, including ‘borealis’, ‘grunowii’ and ‘stomatophora’. We also studied the fatty acid prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…At first glance, P. hupingensis is similar to P. brandelii , but the latter has a lunate marking on either side of the central nodule (see Krammer (2000) , plate 97, figs 7–12), whereas P. hupingensis does not have such lunate markings. Interestingly, Kezlya et al (2022) noted that morphological distinctions, such as the surface markings in the central area, are consistent with phylogenic clades defined by genetic markers. The absence of such markings in P. hupingensis , therefore, excludes the possibility of this taxon being conspecific with P. brandelii .…”
Section: Discussionmentioning
confidence: 71%
“…At first glance, P. hupingensis is similar to P. brandelii , but the latter has a lunate marking on either side of the central nodule (see Krammer (2000) , plate 97, figs 7–12), whereas P. hupingensis does not have such lunate markings. Interestingly, Kezlya et al (2022) noted that morphological distinctions, such as the surface markings in the central area, are consistent with phylogenic clades defined by genetic markers. The absence of such markings in P. hupingensis , therefore, excludes the possibility of this taxon being conspecific with P. brandelii .…”
Section: Discussionmentioning
confidence: 71%
“…Additional studies by Gontcharov et al (2021) explored the taxonomy of the three algal isolates of the Primorsky territory of Russia and the Jilin Province of China following phenotypic and molecular methods, and through phylogenetical analysis, they confirmed them to be a new species, Chloroidium orientalis. Kezlya et al (2022) reported the phylogeny and fatty acid profile of a new species of a diatom, Pinnularia sp., from the forest soils of Vietnam. Maltseva et al (2022) followed a polyphasic approach in exposing the taxonomic identity of a Cyanobacterium, Aliinostoc vietnamicum, from the soils of Vietnam.…”
Section: Algae Of Forest Soilsmentioning
confidence: 99%
“…Chlorophyta members such as Trentepohlia , Cephaleuros , and Phycopeltis have been noted to be dominant genera on leaves by many authors (Rindi et al., 2008; Rindi & Guiry, 2002; Rindi & López‐Bautista, 2008; Thomas, Bhagya, & Thomas, 2017). Additionally, the diversity of algae of various aero‐terrestrial environments such as rocks (Cai, Peng, & Li, 2020; Gómez et al., 2016; Kezlya et al., 2022; Radzi et al., 2019), walls (Shalygin et al., 2017; Sherwood et al., 2019; Soares et al., 2019), asbestos (Rindi & Guiry, 2002), and other structures, including monuments (Abdullin et al., 2021; Kirchhoff et al., 2018), has been studied. Algae have also been explored from subaerial microhabitats, like tree trunks (Kulichová et al., 2014; Neustupa et al., 2011, 2013; Neustupa & Škaloud, 2010; Rindi et al., 2006; Song & Lee, 2014) and plant leaves (Li et al., 2020; Rindi & López‐Bautista, 2008; Thomas, Bhagya, & Thomas, 2017).…”
Section: Soil and Other Aero‐terrestrial Algal Diversity And Its Sign...mentioning
confidence: 99%
See 1 more Smart Citation
“…The first and, for a long time, the only mention of this ecological group in Southeast Asia was the work of Kolkwitz and Krieger (1936) , in which they mention the results from a single soil sample collected under trees, in which they found just a few diatom species. However, the situation has been changing in recent years, reflected in the descriptions of many new species from terrestrial environments of this region like soils or tufts of mosses ( Kezlya et al 2020a , b , 2022a , b ; Rybak et al 2020 , 2022a , b , c ; Glushchenko et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%